Completion Of Diversion As A Form Of Child Through Criminal Investigators By Restorative Justice Approach In Police Office Of Indramayu - Saepudin Saepudin; Umar Ma'ruf (Jurnal Daulat Hukum, 2018)
Children who commit in a criminal offense must be treated humanely in accordance with the best interests of the child means that children in conflict with the law should be restorative justice approach that should be pursued first. Indonesia already has rules to protect, prosper and fulfill the rights of children, among others Act No. 3 of 1997 on juvenile justice, Act No. 23 of 2002 on Child Protection. However, it seems not enough to bring significant changes to the fate of children in conflict with the law, and what to expect in reality often can not be implemented properly. Because outiusan judges are more punitive to the detriment of the child itself. Versioned as a form of juvenile criminal settlement through restorative justice approach needs to be taken into consideration in handling children. This concept involves all parties in order to repair the moral children so that children will no longer repeat his actions, so that children feel children aware of the law that affect the mental development of children.Keywords: Children, Diversion, Restorative Justice.